Pengaruh Stres Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. Kusuma Mulia Plasindo Infitex, Klaten - Bahari, Pratama Yanuar, Farid Wajdi, Drs., M.M.,Ph.D (2016)
The purpose of this study was to determine the effect of work stress and work environment on employee performance using a quantitative approach. The subjects were employees at PT Kusuma Mulia Plasindo Infitex Klaten with a total of 60 respondents, by random sampling technique. This study uses primary data obtained from the respondents' answers in the form of filling the questionnaire is data obtained directly from the object of research. Data analysis techniques include: test instrument consisting of validity and reliability test, classic assumption test consists of normality test, multiple linear regression, t test, F test, and test the coefficient of determination. The study explains that the working environment is a significant positive effect on employee performance and job stress significant negative effect on the performance of employees of PT. Kusuma Mulia Plasindo Infitex Klaten.